PELAKSANAAN SISTEM PEMIDANAAN BERSYARAT BAGI NARAPIDANA - Siti Rahmah (Fakultas Hukum Universitas Islam Indragiri, 2017)
Criminalization is not meant to tell and is not allowed to condemn human dignity, it is a gift of meaning to the criminal in the Indonesian legal system. This provision shall have an effect on the real criminal conduct imposed on the convicted person. Which means that the purpose of punishment should not only be seen to educate the convicted person in the right direction as other members of the community, but also to protect and provide peace for the community, to protect the public. Criminalization must be properly provided in accordance with the personal circumstances of the offenders, conditional may be used as an alternative in the provision of criminal offenses. If conducting guidance and supervision of conditional penalties can dilkasanakan as it would be useful for the convicted and others. Based on Article 1 Paragraph 1 of Law Number 12 Year 1995, Correctional is an activity to conduct guidance of prisoners based on the system, institutional and guidance method which is the end in the criminal justice system